Efficacy of Save Medical Corporation (SMC)-01, a Smartphone App Designed to Support Type 2 Diabetes Self-Management Based on Established Guidelines: Randomized Controlled Trial - Nicholas Leung; Kayo Waki; Satoshi Nozoe; Shunpei Enomoto; Ryo Saito; Sakurako Hamagami; Toshimasa Yamauchi; Masaomi Nangaku; Kazuhiko Ohe; Yukiko Onishi (JMIR Publications, 2024)
BackgroundLifestyle modifications are a key part of type 2 diabetes mellitus treatment. Many patients find long-term self-management difficult, and mobile apps could be a solution. In 2010, in the United States, a mobile app was approved as an official medical device. Similar apps have entered the Japanese market but are yet to be classified as medical devices. ObjectiveThe objective of this study was to determine the efficacy of Save Medical Corporation (SMC)-01, a mobile app for the support of lifestyle modifications among Japanese patients with type 2 diabetes mellitus. MethodsThis was a 24-week multi-institutional, prospective randomized controlled trial. The intervention group received SMC-01, an app with functions allowing patients to record data and receive personalized feedback to encourage a healthier lifestyle. The control group used paper journals for diabetes self-management. The primary outcome was the between-group difference in change in hemoglobin A1c from baseline to week 12. ResultsThe change in hemoglobin A1c from baseline to week 12 was -0.05% (95% CI -0.14% to 0.04%) in the intervention group and 0.06% (95% CI -0.04% to 0.15%) in the control group. The between-group difference in change was -0.11% (95% CI -0.24% to 0.03%; P=.11). ConclusionsThere was no statistically significant change in glycemic control. The lack of change could be due to SMC-01 insufficiently inducing behavior change, absence of screening for patients who have high intention to change their lifestyle, low effective usage of SMC-01 due to design issues, or problems with the SMC-01 intervention. Future efforts should focus on these issues in the early phase of developing interventions. Trial RegistrationJapan Registry of Clinical Trials jRCT2032200033; https://jrct.niph.go.jp/latest-detail/jRCT2032200033